Two-step mechanism of Bruton’s tyrosine kinase membrane recruitment and activation - Rachel A. McAllister; Amy L. Stiegler; Keerthana Chari; Meera Chari; Moitrayee Bhattacharyya; Kallol Gupta (Proceedings of the National Academy of Sciences, 2026)
Peripheral membrane proteins (PMPs) are critical mediators of signaling cascades initiated at the cell surface. Their functions depend on their innate ability to interact dynamically with membranes in response to changing cellular conditions. This membrane recruitment may occur via high-affinity interactions with specific lipids/proteins or via transient, low-affinity interactions with the membrane. These weak and dynamic interactions, which are critical regulators of PMP function, are challenging to capture. Taking Bruton’s tyrosine kinase (BTK), a nonreceptor tyrosine kinase essential for B cell activation, we demonstrate a native mass spectrometry platform to understand lipid-mediated recruitment of PMPs by directly studying it from lipid bilayers customized to target membranes. Our data demonstrate that BTK recognizes phosphatidylserine (PS) independently of phosphatidylinositol (3, 4, 5) phosphate (PIP 3 ) binding. We show that PS-bound BTK retains PIP 3 binding via high-affinity sites, while exhibiting PIP 3 -independent basal membrane recruitment. Biochemical assays show that this PS-mediated recruitment sensitizes BTK to PIP 3 -mediated activation at near-physiological PIP 3 concentrations. Thus, we propose a two-step model for BTK membrane recruitment and activation. A low-affinity interaction with high-copy number PS enables plasma membrane recruitment of BTK and increases its membrane-bound concentration. Upon B cell activation, this prerecruited, membrane-bound BTK population localizes to PIP 3 -rich domains via electrostatic gliding along the membrane, driven by low-affinity PS and high-affinity PIP 3 binding. This indicates a cooperative mechanism in which PS can amplify B cell signaling by increasing membrane-bound BTK levels. Our work demonstrates a general model of regulation of PH domain–containing proteins by weak protein–lipid interactions, which can be extended to other PMPs.